Sensory gating of an embryonic zebrafish interneuron during spontaneous motor behaviors - Knogler, Laura D.; Drapeau, Pierre (Frontiers in Neural Circuits, 2014)
In all but the simplest monosynaptic reflex arcs, sensory stimuli are encoded by sensory neurons that transmit a signal via sensory interneurons to downstream partners in order to elicit a response. In the embryonic zebrafish (Danio rerio), cutaneous Rohon-Beard (RB) sensory neurons fire in response to mechanical stimuli and excite downstream glutamatergic commissural primary ascending (CoPA) interneurons to produce a flexion response contralateral to the site of stimulus. In the absence of sensory stimuli, zebrafish spinal locomotor circuits are spontaneously active during development due to pacemaker activity resulting in repetitive coiling of the trunk. Self-generated movement must therefore be distinguishable from external stimuli in order to ensure the appropriate activation of touch reflexes. Here, we recorded from CoPAs during spontaneous and evoked fictive motor behaviors in order to examine how responses to self-movement are gated in sensory interneurons. During spontaneous coiling, CoPAs received glycinergic inputs coincident with contralateral flexions that shunted firing for the duration of the coiling event. Shunting inactivation of CoPAs was caused by a slowly deactivating chloride conductance that resulted in lowered membrane resistance and increased action potential threshold. During spontaneous burst swimming, which develops later, CoPAs received glycinergic inputs that arrived in phase with excitation to ipsilateral motoneurons and provided persistent shunting. During a touch stimulus, short latency glutamatergic inputs produced cationic currents through AMPA receptors that drove a single, large amplitude action potential in the CoPA before shunting inhibition began, providing a brief window for the activation of downstream neurons. We compared the properties of CoPAs to those of other spinal neurons and propose that glycinergic signaling onto CoPAs acts as a corollary discharge signal for reflex inhibition during movement.